2014
DOI: 10.5962/bhl.title.152704
|View full text |Cite
|
Sign up to set email alerts
|

Management of post-harvest diseases of fruits, vegetables and tuber crops /

Abstract: Chapter 1. APPLE {Malus domestica) 3 Chapter 2. APRICOT {Prunus armeniaca) 17 Chapter 3. BANANA {Musa spp.) 18 Chapter 4. CITRUS {Citrus spp.) 32 Chapter 5. EMBLICA/GOOSEBERRY/AOVLA 45 {Phyllanthus emblica) Chapter 6. GRAPE {Vitis vinifera) 48 Chapter 7. GUAVA {Psidium guajava) 59 Chapter 8. JACKFRUIT {Artocarpus heterophyllus) 67 Chapter 9. LITCHI {Litchi chinensis) 69 Chapter 10. MANGO {Mangifera indica) 71 Chapter 11. PAPAYA {Carica papaya) 83 Chapter 12. PEACH {Prunus persica) 92 Chapter 13. PEAR {Pyrus co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 275 publications
(358 reference statements)
0
2
0
Order By: Relevance
“…Eggs were laid on the tuber surface damaged during harvesting and the first-instar larva burrowed inside the yam. Research at the Central Tuber Crops Research Institute (CTCRI), Trivandrum, India, revealed that A. hartii and Araecerus laevigatus were the key pests of Lesser Yam (D. esculenta) in storage (Pillai and Rajamma 1997). In addition to these two insects, Coffee Bean Weevil, A. fasciculatus, damages tubers of Greater Yam D. alata (Lal and Pillai 1997;Pillai and Rajamma 1997).…”
Section: Yamsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggs were laid on the tuber surface damaged during harvesting and the first-instar larva burrowed inside the yam. Research at the Central Tuber Crops Research Institute (CTCRI), Trivandrum, India, revealed that A. hartii and Araecerus laevigatus were the key pests of Lesser Yam (D. esculenta) in storage (Pillai and Rajamma 1997). In addition to these two insects, Coffee Bean Weevil, A. fasciculatus, damages tubers of Greater Yam D. alata (Lal and Pillai 1997;Pillai and Rajamma 1997).…”
Section: Yamsmentioning
confidence: 99%
“…Research at the Central Tuber Crops Research Institute (CTCRI), Trivandrum, India, revealed that A. hartii and Araecerus laevigatus were the key pests of Lesser Yam (D. esculenta) in storage (Pillai and Rajamma 1997). In addition to these two insects, Coffee Bean Weevil, A. fasciculatus, damages tubers of Greater Yam D. alata (Lal and Pillai 1997;Pillai and Rajamma 1997). In D. alata, 16% of the samples and in D. rotundata 60% of the samples were infested by A. fasciculatus after 2 months of storage.…”
Section: Yamsmentioning
confidence: 99%